Spillover effect of United States monetary policy on Nigeria's financial and macro fundamentals - Patterson C. Ekeocha; Elias A. Udeaja (CBN Journal of Applied Statistics, 2020)
This paper examines spillover effects of U.S monetary policy on macroeconomic fundamentals in Nigeria from January 1985 to December 2018. The study period is partitioned to account for conventional monetary policy (CMP) period, January 1985 to August 2007 and unconventional monetary policy (UMP) period, September 2007 to December 2018. Guided by relevant pretests, we find BEKK-VARMA-CCC-MGARCH as the most appropriate model. The study finds significant spillover effects of U.S CMP and UMP on interest rate, exchange rate and inflation rate in Nigeria. We, however, observe that while CMP may be a significant accelerator of shocks persistence on interest rates and exchange rates, the extent to which the UMP accelerate shocks in inflation rate tends to vary for different measures of quantitative easing. Thus, in addition to past own shocks and past own conditional variance of these macro fundamentals, understanding their dynamics cannot be in isolation of their vulnerability to external shocks and volatility due to spillover effects of monetary actions in other economies. In formulating monetary policy, it is therefore, imperative for the Central Bank of Nigeria to monitor the monetary policy process of the US to hedge against shocks spillovers.
Keywords: E52; E58; F37; F42; 330; Foreign Monetary Policy; Shock Persistence; Spillover Effect; US-Nigeria; VARMA-MGARCH